Pemanfaatan Metode Pembelajaran Bahasa Inggris melalui Media Lagu-lagu untuk Siswa - Sukmawati, Anis; Faruq, Salsabila; Asy’ari, Abu Musa (Lembaga Yasin AlSys, 2023)
English is a language that the whole world has started to learn. Thus the language is also called an international language. In addition, this language has become one of the subjects taught to students in schools, institutions up to universities. Song media will motivate and increase students' learning interest in order to create a pleasant learning atmosphere so that students can understand the material easily. The purpose of this research is to improve English learning methods through song media. The results of this study are that learning English through songs can be a powerful means of improving students' memory and ability to speak English. Song media also influences students' pronunciation and listening skills. this can be proven by the ease with which songs are followed and remembered by students so that the language will stick with itself.